Clinical Evidence of Acupoint Stimulation for Primary Dysmenorrhea: A Systematic Review and Updated Meta-Analysis - Wang Y; Liu L; Wu X; Wu Y; Qin R; Wang M; Zhou B; Sun J; Song Y; Zhang M; Li M; Yu L (Journal of Pain Research)
Yaqi Wang,1 Lu Liu,2 Xiao Wu,1 Yisong Wu,3 Renjie Qin,3 Mingyu Wang,3 Bei Zhou,3 Jingjing Sun,3 Yufan Song,1 Mingmin Zhang,1 Man Li,3 Lingling Yu1 1Institute of Integrated Traditional Chinese and Western Medicine, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, Hubei, People’s Republic of China; 2Department of Acupuncture and Moxibustion, Beijing Hospital of Traditional Chinese Medicine, Capital Medical University, Beijing Key Laboratory of Acupuncture Neuromodulation, Beijing, People’s Republic of China; 3Department of Neurobiology, School of Basic Medicine, Tongji Medical College of Huazhong University of Science and Technology, Wuhan, Hubei, People’s Republic of ChinaCorrespondence: Lingling Yu, Institute of Integrated Traditional Chinese and Western Medicine, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, No. 1095 Jiefang Avenue, Wuhan, Hubei, 430030, People’s Republic of China, Email 527679774@qq.com Man Li, Department of Neurobiology, School of Basic Medicine, Tongji Medical College of Huazhong University of Science and Technology, No. 13 Hangkong Road, Wuhan, Hubei, 430030, People’s Republic of China, Email liman73@mails.tjmu.edu.cnPurpose: Meridian-based acupoint stimulation is increasingly used for primary dysmenorrhea (PD), yet its evidence remains inconsistent. This systematic review aims to evaluate efficacy and safety of both invasive and noninvasive acupoint stimulation for PD through analysis of randomized controlled trials (RCTs).Methods: The PROSPERO registration number is CRD42024586857. PubMed, Excerpta Medica Database (Embase), Allied and Complementary Medicine Database (AMED), Cochrane Central Register of Controlled Trials (CENTRAL), Web of Science, Scopus, VIP Database, China National Knowledge Infrastructure (CNKI), and Wanfang Database were searched up to May 20, 2024. Methodological quality was assessed using the revised Cochrane risk of bias, version 2 tool. Data were synthesized using random-effects models and presented with forest plots. The primary outcomes were assessed based on pain intensity measured using the Visual Analog Scale (VAS) or effective rates, and safety measured by adverse reaction rates. The secondary outcomes included self-reported symptoms and quality of life, uterine hemodynamics, and serum prostaglandin contents.Results: A total of 22 eligible RCTs with 1955 participants (range 44 to 216) were included. Compared with no treatment or sham treatment, acupoint stimulation demonstrated moderate pain reduction (standardized mean difference [SMD] − 2.96, 95% confidence interval [CI] − 4.39 to − 1.53). Compared with non-steroidal anti-inflammatory drugs (NSAIDs), acupoint stimulation showed both immediate effects (post-first-treatment SMD − 2.85, 95% CI − 4.06 to − 1.64) and sustained benefits (3 cycles SMD − 1.58, 95% CI − 2.43 to − 0.73; following 3 cycles SMD − 3.74, 95% CI − 5.57 to − 1.90), particularly with invasive techniques. The incidence of adverse events did not differ significantly between groups (relative risk [RR] 0.94, 95% CI 0.26 to 3.33). The GRADE certainty of the evidence ranged from low to moderate, owing to considerable risk of bias and high heterogeneity.Conclusion: Current evidence suggests that acupoint stimulation may reduce pain intensity in primary dysmenorrhea without increasing adverse reactions, particularly long-term.Keywords: acupoint stimulation therapy, primary dysmenorrhea, acupuncture, acupressure, sham acupuncture, NSAIDs